De novo transcriptome assembly: a new laccase multigene family from the marine-derived basidiomycete Peniophora sp. CBMAI 1063 - Otero, Igor Vinicius Ramos [UNESP] (2017)
Laccases are multicopper oxidases that are able to catalyze reactions involving a range of substrates, including phenols and amines, and this ability is related to the existence of different laccases. Basidiomycetes usually have more than one gene for laccase, but until now, this feature has not been demonstrated in a marine-derived fungus. Peniophora sp. CBMAI 1063 is a basidiomycete fungus isolated from a marine sponge that exhibits the ability to secrete significant amounts of laccase in saline conditions. In the present study, we identified laccase sequences from the transcriptome of Peniophora sp. CBMAI 1063 and used them to perform different molecular in silico analyses. The results revealed the presence of at least eight putative genes, which may encode ten different laccases with peptide lengths ranging from 482 to 588 aa and molecular weights ranging from 53.5 to 64.4 kDa. These laccases seem to perform extracellular activities, with the exception of one that may represent an intracellular laccase. The 10 predicted laccases expressed by Peniophora sp. CBMAI 1063 in laccase-induced media showed different patterns of N-glycosylation and isoelectric points and are divided into two classes based on the residue associated with the regulation of the redox potential of the enzyme. None of the predicted laccases showed more than 61% similarity to other fungal laccases. Based on the differences among the laccases expressed by Peniophora sp. CBMAI 1063, this marine-derived basidiomycete represents a valuable resource with strong potential for biotechnological exploitation.